Class S: appropriation of ‘lesbian’ subculture in modern Japanese literature and New Wave cinema - Shamoon, Deborah (Cultural Studies, 2021)
In the 1920s in Japan, girls attending single-sex secondary schools developed a girls’ culture (shōjo bunka) or subculture to insulate themselves temporarily from the pressures of patriarchal society. Part of this subculture was a practice called s kankei (s or sister relationships), also called Class S, which were same-sex romantic attachments between classmates, condoned at the time as a temporary practice relationship that would end upon graduation, followed by an arranged marriage. Although s relationships were not ‘lesbian’ in the contemporary sense, literature and film created by men in the 1920s through the 1960s appropriated aspects of girls’ culture, including exploitative representation of female homosexuality. One example is Manji (Quicksand, 1928) by Tanizaki Jun’ichirō, which depicts an s relationship as lurid and perverse. Kawabata Yasunari plagiarized from his female disciple Nakazato Tsuneko in order to publish the most popular Class S novel of the era, Otome no minato (Harbor of Girls, 1937). Kawabata also included exploitative scenes of female homosexuality in his novel Utsukushisa to kanashimi to (Beauty and Sadness, 1963). Both Tanizaki’s and Kawabata’s novels were made into films by New Wave directors, Manji in 1964 by Masumura Yasuzō and Beauty and Sadness in 1965 by Shinoda Masahiro, and featured the first depictions of ‘lesbianism’ in Japanese film. Although these films reinscribe the male gaze, they helped inspire a nascent gay culture and opened the way for more authentic gay cinema. This essay recenters girls’ culture in modern Japanese literature and film, and discusses the variable meaning of female homosexuality for different audiences.
Keywords: approches et analyses; arts; asie; discipline; discours dominant; japon; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; systèmes d'oppressions; études culturelles; études littéraires

Sémi: roman - Shimazaki, Aki (Actes Sud, 2021)
« Après plus de quarante ans de mariage, Tetsuo et Fujiko se sont installés en maison de retraite car Fujiko, atteinte de la maladie d’Alzheimer, requiert une prise en charge particulière. Un matin, au réveil, elle ne reconnaît plus son époux. D’abord en grand désarroi, Tetsuo entreprend finalement de reconquérir celle qui le prend désormais pour un étranger auquel elle se trouve simplement fiancée. »– Site de l'éditeur
Section: 150 pages ; 19 cm.
Keywords: arts; asie; care; cours; discipline; japon; lit2815; premier cycle; roman; régions géographiques; thématiques; écriture des femmes*; études littéraires

Masculinity, race and national identity: representations of non-Japanese men’s speech in contemporary Japanese novels - Suzuki, Satoko (Gender and Language, 2020)
Language ideologies have been of central concern to the study of Japanese language, gender and society. Many scholars have researched ideologies surrounding representations of Japanese women’s speech; however, investigations of representations of men’s speech have been limited. This study contributes to filling this gap through the analysis of non-Japanese male characters found in contemporary Japanese novels. The article reveals that authors assign strongly masculine expressions to their East Asian characters much more frequently than to their white characters and argues that these differentiated representations of non-Japanese male characters’ speech reproduce and are influenced by ideologies concerning cultural nationalism, racial determinism, class and sexuality. Linguistic data are presented that both unsettle the constructed image of Asian males as asexual beings and question the historically assumed relationship between gendered language and authenticity.
Keywords: arts; asie; cours; discipline; histoire et politique; japon; lin2685; linguistique; masculinité; premier cycle; représentation des hommes; régions géographiques; sciences humaines; sofia; thématiques; études littéraires

Témoin de la nuit: roman - Desai, Kishwar; Dauvergne, Benoîte (Éd. de l'Aube, 2013)
Simran Singh est chargée d'une affaire délicate : une adolescente est retrouvée dans la luxueuse maison familiale, bâillonnée et brûlée après avoir été violée. Autour d'elle, treize cadavres empoisonnés. Bientôt, la police soupçonne la jeune fille ! À charge pour Simran de découvrir la vérité, dans une société où naître fille peut s'avérer dangereux…
Section: 1 vol. (228 p.) : couv. ill. ; 22 cm.
Keywords: 2000 à aujourd'hui; Roman policier; arts; asie; cours; discipline; inde; lit2815; premier cycle; périodes historiques; roman; régions géographiques; thématiques; violences; écriture des femmes*; études littéraires

Ru - Thúy, Kim (Libre Expression,une compagnie de Quebecor Media, 2009)
« "Le paradis et l'enfer s'étaient enlacés dans le ventre de notre bateau. Le paradis promettait un tournant dans notre vie, un nouvel avenir, une nouvelle histoire. L'enfer, lui, étalait nos peurs : peur des pirates, peur de mourir de faim, peur de s'intoxiquer avec les biscottes imbibées d'huile à moteur, peur de manquer d'eau, peur de ne plus pouvoir se remettre debout, peur de devoir uriner dans ce pot rouge qui passait d'une main à l'autre, peur que cette tête d'enfant galeuse ne soit contagieuse, peur de ne plus jamais fouler la terre ferme, peur de ne plus revoir le visage de ses parents assis quelque part dans la pénombre au milieu de ces deux cents personnes." Ru est le récit d'une réfugiée vietnamienne, une boat people dont les souvenirs deviennent prétexte tantôt à l'amusement, tantôt au recueillement, oscillant entre le tragique et le comique, entre Saigon et Granby, entre le prosaïque et le spirituel, entre les fausses morts et la vraie vie. »– Quatrième de couverture.
Section: 144 pages ; 23 cm
Keywords: amériques; approches et analyses; arts; asie; boat people; canada; cours; discipline; histoire et politique; immigration; lit3220; littérature; premier cycle; québec; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; vietnam; écriture des femmes*; études littéraires

Quand les femmes écrivent la guerre : transformation du genre et du monde dans Les hommes qui marchent de Malika Mokeddem et Iran, les rives du sang de Fariba Hachtroudi - Bélanger, Marie-Ève (Université du Québec à Montréal, 2005)
Keywords: 1900-1999; 1990-1999; IREF; afrique; algérie; asie; discipline; guerre; iran; mémoires/thèses; périodes historiques; régions géographiques; thématiques; violences; écriture des femmes*; études littéraires

Quatre mille marches - Chen, Ying (Boréal, 2004)
« Romancière avant tout, Ying Chen a tout de même rédigé, au fil des ans, des textes dans lesquels elle tente de réfléchir simplement, modestement, en adoptant le mode de l’interrogation, du souvenir et de la lettre familière plutôt que celui de l’analyse ou de la théorie, à ce que sont pour elle - et peut-être pour ses lecteurs - la portée et la signification de son art, le sens de son itinéraire personnel de femme, d’exilée et d’écrivain, ou la place de la littérature dans le monde éclaté d’aujourd’hui. Il en résulte une série d’essais brefs, écrits dans une prose aussi sobre que directe, qui constituent d’une certaine manière l’accompagnement ou l’écho méditatif de cette parole qui se fait entendre dans ses romans et à travers la voix des personnages auxquels elle a donné vie. »
Section: 126 pages ; 22 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; arts; asie; chine; cours; discipline; lit2815; lit3495; point de vue situé; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires